2019
DOI: 10.15252/embj.2018100156
|View full text |Cite
|
Sign up to set email alerts
|

Cideb controls sterol‐regulated ER export of SREBP / SCAP by promoting cargo loading at ER exit sites

Abstract: SREBP s are master regulators of lipid homeostasis and undergo sterol‐regulated export from ER to Golgi apparatus for processing and activation via COPII ‐coated vesicles. While COPII recognizes SREBP through its escort protein SCAP , factor(s) specifically promoting SREBP / SCAP loading to the COPII machinery remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…Srebp forms are retained in the endoplasmic reticulum (ER) by a complex with the cholesterol sensor, Scap. This complex transfers to the Golgi for cleavage to the active nuclear form when cholesterol becomes depleted [90]. Srebp activation is also stimulated via the multi-protein mTORC1 complex, a sensor of metabolic homeostasis [76,91,92].…”
Section: A Systems Approach To Gvad-cyp1b1 Regulationmentioning
confidence: 99%
“…Srebp forms are retained in the endoplasmic reticulum (ER) by a complex with the cholesterol sensor, Scap. This complex transfers to the Golgi for cleavage to the active nuclear form when cholesterol becomes depleted [90]. Srebp activation is also stimulated via the multi-protein mTORC1 complex, a sensor of metabolic homeostasis [76,91,92].…”
Section: A Systems Approach To Gvad-cyp1b1 Regulationmentioning
confidence: 99%
“…SREBP is initially synthesized as a precursor protein with the N- and C-terminal ends facing the cytosol and two transmembrane segments spanning the endoplasmic reticulum (ER). Upon cholesterol depletion, SREBP and the associated SREBP-cleavage activating protein (SCAP), with the help of Cideb, rapidly translocate from the ER to the Golgi apparatus (Su et al, 2019 ). At the Golgi, SREBP is cleaved by site-1 protease (S1P) in the lumenal loop followed by a second cleavage by site-2 protease (S2P) within the membrane-spanning domain (Brown and Goldstein, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in response to ER stress, SREBPs overexpression increased the expression of cholesterolgenic and lipogenic gene, resulting in cholesterol and lipid accumulation and provoking consequent apoptosis. Three potential mechanisms by which ER stress induces SREBP activation: caspase-induced SREBP cleavage (Colgan, 2007), eIF2α-phosphorylation-dependent downregulation of INSIG (Birkenfeld et al, 2011) and GRP78 dissociation from the SCAP-SREBP complex (Su et al, 2019). Previous studies showed that in vitrooverexpression of GRP78 could decrease markers of ER stress, attenuate ER-stress-induced SREBP activation and lipid accumulation (Lhoták et al, 2012).…”
Section: Discussionmentioning
confidence: 99%